Floristic-structural variations of a tree community associated to edge distance in a forest patch in "Planalto Sul Catarinense" region Variações florístico-estruturais da comunidade arbórea associadas à distância da borda em um fragmento florestal no Planalto Sul-Catarinense - Pscheidt F.* (2015)
In order to compare the floristic-structural organization of a tree species community in an Araucaria Forest patch, in the municipality of Lages, SC, a phytossociological survey was conducted in five 100 × 20 m transections, subdivided into 10 × 20 m plots, perpendicular to the patch edges. It were measured and determined all trees with circumference at breast height (dbh) ≥ 15,7 (cbh and height). The data were analyzed by the importance value index (IVI), Detrended Correspondence Analysis (DCA); non-parametric multivariate analyze of variance (NPMANOVA); mean values of abundance, basal area, tree height, richness, diversity and evenness; and frequency of individuals within diameter and height classes. Although both sectors had Araucaria angustifolia (Bertol.) Kuntze and Lithraea brasiliensis Marchand among the species with the highest IVI values, there was a turnover in other IVI positions, which reflected in the variation of tree species organization among sectors (p=0.022), also observed in DCA. Related to community structure (mean values of abundance and tree height and individuals frequency in size classes), no differences were detected. We conclude that edges represented an important source of floristic-structural heterogeneity in the studied patch.